Human Resource Practices and Their Financial Impact on Indonesian Banks - Muliahadi Tumanggor; Sri Murtiana; Suwito Suwito; Kasmad Kasmad; Muhammad Saddam (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to analyze the influence of human resource management practices, economic indicators, and tax compliance on the financial performance of Indonesian banks operating in international markets. This study uses quantitative research methods to examine the influence of human resource management practices, economic indicators, and tax compliance on the financial performance of Indonesian banks operating in international markets. Data were collected from 46 banks listed on the Indonesia Stock Exchange through questionnaires and secondary sources. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (SmartPLS 3.0). The results show that human resource practices have a significant positive effect on economic indicators and tax compliance. These two variables directly improve bank financial performance and also mediate the relationship between human resource practices and financial performance. These findings confirm that integrating human resource strategies with economic dynamics and regulatory compliance is crucial in enhancing bank competitiveness in the global market. This study suggests that banks need to invest resources in employee training and strengthening compliance systems to optimize financial performance. This study expands understanding of the mediating role of external indicators in the relationship between human resource practices and organizational outcomes.